2019
DOI: 10.33064/42lm20192244
|View full text |Cite
|
Sign up to set email alerts
|

Specification of a self-care model

Abstract: En términos generales, la promoción del autocuidado obedece a las guías de organizacionesinternacionales que buscan reducir el gasto social en atención médica, pero con énfasis en laresponsabilidad personal. El objetivo del presente trabajo es discutir esta fórmula, estableciendo unmodelo para el estudio del fenómeno. Se realizó una investigación documental con un muestreo noprobabilístico de fuentes indexadas en repositorios internacionales, considerando su publicación yla inclusión de conceptos como &quo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Conducted a study that correlated the prominence of media, public and political arguments. They established positive partnerships between public and political arguments with media arguments in three amplitude levels; low, medium and high [35]. When comparing media discourses of high and low influence, the authors found that the associations were significant at one level of intermediate range, neither too high nor too low.…”
Section: Framing Studiesmentioning
confidence: 96%
“…Conducted a study that correlated the prominence of media, public and political arguments. They established positive partnerships between public and political arguments with media arguments in three amplitude levels; low, medium and high [35]. When comparing media discourses of high and low influence, the authors found that the associations were significant at one level of intermediate range, neither too high nor too low.…”
Section: Framing Studiesmentioning
confidence: 96%
“…¿Existen diferencias significativas entre la estructura teórica reportada en la literatura revisada de la gestión del conocimiento con respecto a la estructura empírica observable en el aprendizaje inmersivo o en la extensión del aprendizaje tradicional? Las premisas que guían el presente trabajo sugieren que las políticas anti COVID-19 diversificaron los riesgos más que mitigarlos (GARCÍA LIRIOS et al, 2019b). Por consiguiente, el aprendizaje inmersivo debió exacerbar en el aula virtual, pero la impericia obligó la importación de los recursos tradicionales de enseñanza y aprendizaje como la exposición mediante Power Point.…”
Section: Introductionunclassified
“…A model is a representation of the relationships between the factors used in the theory. Promoting self-care, indicated by trustworthiness, agenda setting, and co-responsibility, implies an emotional process and a rational treatment of information about a public health problem such as an epidemic or pandemic (Molina et al, 2019). This is so because, although it is a biochemical phenomenon, it becomes a public health problem by involving political and civil actors in the goals, tasks, and objectives of health professionals, who may have access to the media, but they are replaced by communicators, journalists, presenters, reporters, columnists or informants on the public health problem.…”
Section: Introductionmentioning
confidence: 99%